Pengembangan Modul Pembelajaran Pengantar Studi Islam: Studi pada Mahasiswa STAI Ali bin Abi Thalib Surabaya - Maryono, Maryono; Nuha, Zaki Ulien; Bamualim, Mubarak (MASALIQ, 2025)
This study aims to develop a learning module for the course Pengantar Studi Islam (Introduction to Islamic Studies) at the Ali bin Abi Thalib Islamic College (STAI) Surabaya, focusing on the sources of Islamic teachings: the Qur'an, Sunnah, Ijma', and Qiyas. The method used is Research and Development (R&D) with the Rowntree development model, which involves three stages: planning, development, and evaluation. Data were collected through expert validation, student questionnaires, and formative evaluation. The results of the study show that the developed module is valid, with an average score of 94% from content experts and 95.5% from language experts. It was also deemed very practical by students, with an average score of 82.82%. The module has proven to meet learning needs by providing structured material, communicative language, and relevant exercises. Suggestions from validators and students were implemented to enhance the quality of the module, making it more suitable for the learning context. The conclusion of this study indicates that the developed PSI learning module is valid, practical, and feasible for use in improving the quality of learning. This research is expected to serve as a reference for the development of similar teaching materials in the future.